Genetic association analysis reveals significant effect of β-casein A1/A2 loci on production & reproduction traits in Frieswal crossbred cows. Issue 8 (16th November 2020) - Kumar, Adesh; Singh, Ran Vir; Chauhan, Anuj; Ilayakumar, K; Kumar, Sushil; Kumar, Amit; Sonwane, Arvind; Kumar, Subodh; Panigrahi, Manjit; Bhushan, Bharat
ABSTRACT: Milk β-casein has attracted extensive research interest in the dairy industry and animal breeding as a source of high-quality protein for human diet; however, adverse health effects have been ascribed to A1 β-casein variant consumption. A study was conducted to genotype the polymorphism in milk β-casein gene and examines the potential association between β-casein genotypes and milk production and reproduction traits in population of Frieswal cows. β-Casein A1/A2 genotype had significant effect (P ≤ 0.05) on several production traits including Total Milk Yield (TMY) (P ≤ 0.05), Milk Milk yield 300 days (MY300) (P ≤ 0.05), Lactation Length (LL) (P ≤ 0.01) and Peak Yield (PY) (P ≤ 0.01). β-Casein A1A1 genotype cows had significantly lower TMY, MY300, PY and DP as compared to A1A2 and A2A2 genotypes. A1A2 genotype had highest TMY, MY300, PY and DP; however, A2A2 and A1A2 genotypes were not significantly different from each other. The results pointed towards the superiority of A2 β-casein variant for several production traits in crossbreds. Further, with higher price of A2 milk, the inclusion of β-casein A1/A2 genotype in the selection of crossbreds offers higher profitability from dairy enterprise as well as provides a nutritional wellness product for consumers.